Speech Production in Speech Technologies: Introduction to the CSL Special Issue. (March 2016) - Livescu, Karen; Rudzicz, Frank; Fosler-Lussier, Eric; Hasegawa-Johnson, Mark; Bilmes, Jeff
Abstract: Aspects of speech production have provided inspiration for ideas in speech technologies throughout the history of speech processing research. This special issue was inspired by the 2013Workshop on Speech Production in Automatic Speech Recognition in Lyon, France, and this introduction provides an overview of the included papers in the context of the current research landscape.